Theoretical analysis and mitigation of inter-carrier interference in orthogonal frequency division multiplexing system - Ng, Wee Teck (2008)
One of the main problems of high data rate transmission over wireless channel is the delay spread. Orthogonal Frequency Division Multiplexing (OFDM) system, which is robust against multipath propagation, is often employed for such hostile wireless environments. However, due to fast time varying (Doppler spread) channels, the performance of OFDM system degrades considerably. It is found that by using directional antenna or beamforming, the amount of Doppler spread can be reduced. To investigate the effect, Doppler Power Spectral Density (PSD) equations are derived where directional antennas are employed at the mobile or/and the base station. The Doppler PSDs are derived for two different Doppler spread channel models, the two dimensional (2-D) and three dimensional (3-D) models. The 2-D model considers only the azimuthal plane, whereas the 3-D model takes into account the effect of both azimuthal and elevation planes. The 2-D model is derived from the popular classical Clake/Jakes' model, whereas the 3-D model is extended from the uniform Doppler spread model.